2007
DOI: 10.3758/bf03193147
|View full text |Cite
|
Sign up to set email alerts
|

Word naming and psycholinguistic norms: Chinese

Abstract: 192Recent research has shown that many variables affect speakers' performance in word-naming tasks. As Balota, Cortese, Sergent-Marshall, Spieler, and Yap (2004) pointed out, such variables could include factors at various levels-for example, the surface level (initial phoneme), the lexical level (e.g., word length, word frequency, and spelling-to-sound consistency), and the semantic level (e.g., imageability and concreteness). These levels are not mutually exclusive and in fact sometimes overlap with one anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
193
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(217 citation statements)
references
References 31 publications
22
193
2
Order By: Relevance
“…Character frequency A considerable amount of evidence has indicated that character frequency is a powerful predictor of RTs in Chinese character recognition; frequency effects have been observed consistently in a wide range of tasks (Hue, 1992;Lee et al, 2005;Liu et al, 2007;Yang et al, 2009). Higher frequency characters tend to be processed more quickly than lower frequency characters during naming (Lee et al, 2005;Yang et al, 2009).…”
Section: Lexical Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…Character frequency A considerable amount of evidence has indicated that character frequency is a powerful predictor of RTs in Chinese character recognition; frequency effects have been observed consistently in a wide range of tasks (Hue, 1992;Lee et al, 2005;Liu et al, 2007;Yang et al, 2009). Higher frequency characters tend to be processed more quickly than lower frequency characters during naming (Lee et al, 2005;Yang et al, 2009).…”
Section: Lexical Variablesmentioning
confidence: 99%
“…Regarding Chinese, only recently have large-scale psycholinguistic norms for simplified Chinese characters been developed (Liu, Shu, & Li, 2007;Sze, Rickard Liow, & Yap, 2013). Liu et al provided the first large-scale database of simplified Chinese character naming.…”
mentioning
confidence: 99%
See 3 more Smart Citations